Social movements and referendums from below : direct democracy in the neoliberal crisis /: direct democracy in the neoliberal crisis. (2017) - Della Porta, Donatella, 1956-; (Writer on neoliberalism), O'Connor, Francis; Portos, Martin; Subirats, Anna
No abstract available